Vocabulary and Grammar Gains Through AzVocab.AI Integration in Writing: Kosakata dan Tata Bahasa Diperoleh Melalui Integrasi AzVocab.AI dalam Penulisan - Mulyani, Agustina; Darmawan, Deni; Rahayu, Ayu Puji (Indonesian Journal of Innovation Studies, 2025)
General Background: Writing is a core English skill that requires mastery of vocabulary and grammar, yet students often struggle in both areas. Specific Background: At SMPN 2 Limbangan Garut, many eighth-grade students fail to meet writing performance standards due to limited vocabulary and grammar proficiency. Knowledge Gap: Despite the proliferation of AI tools in education, little is known about their effectiveness at the junior high school level in Indonesia, particularly in writing skills development. Aims: This study aims to evaluate the effectiveness of AzVocab.AI, an AI-powered vocabulary learning platform, in improving students’ writing outcomes through enhanced vocabulary and grammar acquisition. Results: Using a true experimental design with three learning cycles (pretest-treatment-posttest), the study found a consistent improvement in scores: vocabulary increased from 41.25 to 75.5 and grammar from 46.25 to 75.5. N-Gain scores were moderate, while regression analysis showed AzVocab.AI accounted for 77.9% of the vocabulary gains and 47.5% for grammar. Novelty: The study presents one of the first empirical validations of an AI-based tool’s impact on junior high school writing performance in Indonesia. Implications: These findings suggest integrating AzVocab.AI into English curricula could significantly enhance student autonomy and language skill development in secondary education settings.Highlight : AzVocab.AI significantly improved students’ vocabulary and grammar scores with a moderate N-Gain category. The platform supports self-directed learning by offering real-time feedback and contextual vocabulary exercises. Regression analysis showed AzVocab.AI contributed 77.9% to vocabulary improvement and 47.5% to grammar enhancement. Keywords : AzVocab.AI, Vocabulary, Grammar, Writing Skill, Educational Technology